2021
DOI: 10.1007/s10916-021-01726-7
|View full text |Cite
|
Sign up to set email alerts
|

Non-pharmaceutical Interventions and the Infodemic on Twitter: Lessons Learned from Italy during the Covid-19 Pandemic

Abstract: The COVID-19 pandemic changed expectations for information dissemination and use around the globe, challenging accepted models of communications, leadership, and social systems. We explore how social media discourse about COVID-19 in Italy was affected by the rapid spread of the virus, and how themes in postings changed with the adoption of social distancing measures and non-pharmaceutical interventions (NPI). We used topic modeling and social network analysis to highlight critical dimensions of conversations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 43 publications
(20 reference statements)
0
20
0
1
Order By: Relevance
“…Using SNA as an analysis method can support emergency agencies in their understanding of the network structure of user interactions as situations rapidly emerge (Leon et al , 2020; Zhu and Wang, 2020). Using SNA to analyse the network on the COVID-19 pandemic includes COVID-19 transmission analysis based on the citizen interaction community network (Jo et al , 2021; Obadimu et al , 2021; Yie et al , 2021) and information spreading on social media (Ahmed et al , 2020; Al-Shargabi and Selmi, 2021; Bahja and Safdar, 2020; Gruzd and Mai, 2020; Massaro et al , 2021). Studies applied SNA on the topic of COVID-19 mainly focused on the centrality degree (betweenness centrality, closeness centrality, eigenvector centrality), PageRank, cohesive subgroups and core periphery of the networks to detect key nodes in the networks.…”
Section: Related Workmentioning
confidence: 99%
“…Using SNA as an analysis method can support emergency agencies in their understanding of the network structure of user interactions as situations rapidly emerge (Leon et al , 2020; Zhu and Wang, 2020). Using SNA to analyse the network on the COVID-19 pandemic includes COVID-19 transmission analysis based on the citizen interaction community network (Jo et al , 2021; Obadimu et al , 2021; Yie et al , 2021) and information spreading on social media (Ahmed et al , 2020; Al-Shargabi and Selmi, 2021; Bahja and Safdar, 2020; Gruzd and Mai, 2020; Massaro et al , 2021). Studies applied SNA on the topic of COVID-19 mainly focused on the centrality degree (betweenness centrality, closeness centrality, eigenvector centrality), PageRank, cohesive subgroups and core periphery of the networks to detect key nodes in the networks.…”
Section: Related Workmentioning
confidence: 99%
“…As a result, in the last several years, the use of big data analytics to make sense of the tremendous volume of first-hand user-generated information accumulated on social media is becoming increasingly popular [e.g., 3 , 16 , 17 19 ]. Amongst social media platforms, Twitter has been the platform of most interest to researchers [ 20 ].…”
Section: Background and Related Workmentioning
confidence: 99%
“…For instance, the focus of Lyu and Luli [ 22 ] and Li et al [ 24 ] was on the United States where the former extracted the topics and overarching themes emerging from the public COVID-related tweet discussion about the Centers for Disease Control and Prevention, and the latter used Twitter posts to detect stress symptoms related to COVID-19 in the US. Others have studied Italy [ 17 ], Brazil [ 25 ], China [ 26 ], the Arab region [ 27 ], and so on (See Table 1 ). Given the domestic focus of these studies, many have investigated languages other than English, for example Alshalan, et al [ 27 ] examined around 14 million Arabic tweets and identified fifteen public concerns and government pandemic measures as well as six macro-concerns.…”
Section: Background and Related Workmentioning
confidence: 99%
“…The NPIs adopted also included early case isolation, social distancing, using face masks, and closing schools and businesses. These strategies limited virus-related mortality, and prevented local healthcare systems from being overwhelmed [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The surveillance systems began collecting records on January 4, but schools only reopened on 7 January 2021 2. From March 10, attendance was suspended locally for all high schools and the second and third years of middle schools (for 12 and 13-year-olds) if the local cumulative weekly incidence of infections exceeded 250 per 100,000 population, in accordance with national legislation.…”
mentioning
confidence: 99%